(untitled) (European Journal of Child Development, Education and Psychopathology, 2019)
Separation and divorce processes suppose a restructuration of family relationships, of the ways of convivence and the habits of all family members. Sometimes, these familly processes becomes in a conflictive situation that developes as a contentious judicial process. The existence of an increased risk of maladjustment in sons and daughters of couples in high conflictive separation or divorce processes have been documented. They frecuently experience more difficulties in some contexts, as personal, social and specifically in academic environment. Our investigation, conducted on 246 sons and daughters whose parents were in separation or divorce processes, aged between 8 and 18, showed a predominance of dissatisfaction with parents relationship, in addition to higher levels of school maladjustment, especially in the case of male and increasing in older boys. Our conclusions are that there are differences in school adjustment of students whose parents are involved in high conflict separation or divorce processes. Sex and age may be related factors, with girls better adapted, as well as younger boys.